Даль памяти народной - Прокушев Юрий Львович (Советская Россия, 1983)
Экземпляры: (20200204) / Инвентарный номер: 8544 / Цена: 0.80 / Сис.шифр: 83.3(2Рос=Рус)-8 / Авт.знак: П 80 / ББК: 83.3(2Рос=Рус)-8